Upaya Meningkatkan Kesadaran Pelaku UMKM Dalam Membayar Pajak Penghasilan Final - Isna Khoirinnisa (Public Service and Governance Journal, 2023)
Tax is the biggest source of income for a country in funding the State Budget (APBN). The very large number of MSMEs in Indonesia have a very large potential for levy revenue, so that public authorities must boost levy revenue from MSMEs. However, a significant problem that must be addressed is that the majority of business actors are not registered as taxpayers and do not pay. The purpose of this study is to explain efforts so that business people know more about how to pay their taxes. The preparation of this conceptual article uses a literature review approach. Data collection was carried out by searching and collecting literature sourced from journal articles which were then presented using descriptive analysis. The results of this study indicate that efforts to increase the awareness of MSME actors in paying taxes can use a strategy in the form of outreach about taxation, updating the tax service system, transparency in the management and utilization of tax funds, and making policies or sanctions for MSME actors who do not comply with tax payments.